2007
DOI: 10.1016/j.bbrc.2007.02.075
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance protein 1 is not associated to detergent-resistant membranes

Abstract: Multidrug resistance protein 1 (MRP1) is a member of the ATP-binding cassette superfamily. Using the energy provided by ATP hydrolysis, it transports a broad spectrum of substrates across the plasma membrane, including hormones, leukotriene C 4 , bile salts, and anti-cancer drugs.Recent works have suggested that P-glycoprotein is associated to cholesterol and sphingolipid-rich membrane microdomains and that cholesterol upregulates its ATPase and drug transport activities. Confocal microscopy experiments and Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In this model, vesiculation may be induced by enriched in rafts ( 27,35 ). It has been shown that ABCA1 and ABCC1 are not associated with membrane raft domains ( 39,40,50,51 ), while ABCG2 is located in membrane rafts ( 44 ). Although ABCB1 has been reported to exist in rafts and nonraft membrane domains, depending on the cell type, experimental conditions, and methods, it is generally accepted that ABCB1 is marginally associated with TXI membranes ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this model, vesiculation may be induced by enriched in rafts ( 27,35 ). It has been shown that ABCA1 and ABCC1 are not associated with membrane raft domains ( 39,40,50,51 ), while ABCG2 is located in membrane rafts ( 44 ). Although ABCB1 has been reported to exist in rafts and nonraft membrane domains, depending on the cell type, experimental conditions, and methods, it is generally accepted that ABCB1 is marginally associated with TXI membranes ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 18 20 In the case of MRP1, there are some controversies about the presence of this transporter in lipid rafts. 21 23 …”
Section: Introductionmentioning
confidence: 99%